Ocular Melanocytosis and Glaucoma in a Shih Tzu Dog - Carvalho, Renato Luís; Voitena, Jéssica Naiara; Marinho, Tatiane Ozório Campagnoli; Silva, Victoriana Khadigia de Andrade; da Cunha, Olicies; Brito, Fábio Luiz da Cunha (Acta Scientiae Veterinariae, 2024)
Background: Ocular melanocytosis was originally described as pigmentary glaucoma and reported in seven dogs of the Cairn Terrier breed. Subsequently, the occurrence of this condition was reported in other breeds of dogs among them a Shih Tzu, recently described. With progression, black pigment spots in the sclera and episclera cover the ciliary cleft. Pigment particles can often be seen suspended in the aqueous and, as they sediment, cover the ventral drainage angle, causing secondary glaucoma. The aim of this study was to describe the clinical and sonographic findings of a Shih Tzu dog with melanocytosis and unilateral secondary glaucoma. Case: A 8-year-old, male, Shih Tzu dog, with a history of progressive darkening of the sclera for 5 years, was referred to the ophthalmological service. The patient underwent routine ophthalmic examination. Slit lamp biomicroscopy revealed anisocoria. In the right eye, diffuse pigmentation of the sclera was observed in almost the entire perilimbal region, and in the iris signs of advanced atrophy with tissue loss between 9 h and 12 h. Nevertheless, zonular ligaments could be observed in this region, as well as a large amount of pigment deposits in the ventral region of the ciliary cleft. Applanation tonometry showed intraocular pressure (IOP) of 14 mmHg. Fundoscopic examination did not reveal abnormal pigmentation, but attenuation of the retinal vessels and in the optic disc was observed. In the left eye, no change was observed to demonstrate the bilaterality of the disease. One month later, the patient returned to the ophthalmology service complaining of an increase in the size of the right eye. Ophthalmic examination revealed moderate buftalmia in the right eye, IOP of 30 mmHg and increased ocular melanosis. Treatment was instituted to control intraocular pressure. Fifteen days after the start of treatment, the IOP decreased to 18 mmHg and it was found that the ophthalmic signs had improved, with a decrease in ocular discomfort. Ultrasound examination showed an increase in the anteroposterior axis and expansion of the anterior chamber, with scattered hyperechogenic spots in the periphery. Ultrasound biomicroscopy (UBM) was performed, in which the presence of obstruction in the ciliary fissure and the presence of punctate echoes between the ciliary fissure and the iris were observed. Four months later, the ophthalmic signs were stable, as well as the IOP (20 mmHg). Currently, the animal is visual in both eyes and with a stable condition in the progression of the disease. Discussion: This condition also known as melanocytosis, pigmentary glaucoma or abnormal pigment deposition, involves the gradual accumulation of pigment-laden cells mainly, melanocytes but also melanophages, in the anterior segment structures including the iris and ciliary body. It is seen in dogs of the Cairn Terriers breed as a hereditary defect, but has been reported in other breeds. Recently the condition was reported in a Shih Tzu, however differently from our work where the condition was unilateral and with a controllable glaucoma. The disorder initially manifests clinically with a progressive bilateral dark peripheral thickening of the iris base, followed by scleral/episcleral plaques of pigment adjacent to the limbus. Signs increase slowly, with pigment clusters in the aqueous and pigmentation in the ventral iridocorneal angle and peripheral endothelium, symptoms are usually bilateral, although not always symmetrical. This is the 1st case of a Shih Tzu with melanocytosis and controlled secondary glaucoma, unilateral, reported in the literature. This is a disease that should be considered as a differential diagnosis of uveal melanomas and melanocytomas. Keywords: pigmentation, pigmentary glaucoma, sclera. Título: Melanocitose ocular e glaucoma em cão da raça Shih Tzu Descritores: pigmentação, glaucoma pigmentar, esclera.